Inclusivity and Social Status Representation in Rucas’s TikTok Content as a Branding Strategy - Rahmadina Aulia; Rocky Prasetyo Jati (Journal of Digital Marketing and Communication, 2026)
Despite the growing scholarly attention to TikTok as a branding platform, there remains a gap in understanding how local fashion brands construct inclusivity through visual representation of marginalized social groups—particularly informal workers. This study addresses this gap by examining @rucas.official, an Indonesian fashion brand whose transformation content has attracted 1.9 million followers and 129.6 million likes, making it a significant yet underexplored case of emotional branding through social representation. Using Stuart Hall’s encoding–decoding model, this article analyzes how Rucas constructs meanings of inclusivity and social status in transformation videos featuring waste pickers and parking attendants, and how audiences interpret those meanings. The analysis draws on visual observation of selected TikTok videos, documentary data, and public comment analysis. Findings reveal that Rucas encodes inclusivity through three structured phases: the before phase (social reality), the process phase (dignity and care), and the after phase (identity transformation through streetwear aesthetics). Audience responses reflect dominant, negotiated, and oppositional readings. The study concludes that inclusive branding on short-form video platforms can deepen emotional engagement, but must be accompanied by ethical transparency regarding consent, compensation, and long-term well-being of the subjects portrayed.